STRATEGIC IMPACTS OF INFORMATION TECHNOLOGY INVESTMENTS ON BANKING INDUSTRY PERFORMANCE: EVIDENCES FROM A CROSS-COUNTRY ANALYSIS FOR BRAZIL, UNITED STATES, ARGENTINA, URUGUAY AND CHILE - Lerch Lunardi, Guilherme; Becker, João Luiz; Gastaud Maçada, Antonio Carlos (Revista Eletrônica de Administração, 2013)
More and more industrial and services organizations have invested time, money and their own future in Information Technology (IT). Banks, in particular, have spent billions of dollars in IT, having their products and services basically supported by it. Identifying the IT investments and its impact is a very important point for the bank executives. This study evaluates the strategic effects of IT in Brazilian, American, Argentinean, Uruguayan and Chilean banks as perceived by their executives. The sample included 334 executives and the proposed framework evaluated ten different variables. In order to externally validate the questionnaire, results were analyzed considering, as isolated samples, (a) Brazil, (b) the United States, (c) Argentina, Uruguay and Chile, and, then, (d) as one group merging all data. The results highlight that (1) Competition, Products and Services, and Borrowers (Customers) are the main strategic variables affected by IT; in order to detect similar and distinct perceptions among the different countries’ managers, we observed (3) Argentinean and Uruguayan, American and Uruguayan, and Brazilian and Argentinean executives have a very similar perception of IT impacts on banks; on the other hand, Brazilian and American executives present distinct perception.